Socialium or the Financial Price of Social Responsibility - POP, Diana; MARIE-JEANNE, CAROLINE; DUMOULIN, RÉGIS (Bankers, Markets & Investors, 2024)
We investigate whether investors are willing to pay higher prices to invest in social projects, a differential that we call socialium. Using matching procedures on samples of social and conventional bonds of transnational organisations, we find that, on average, there is no yield and spread differentials on the primary and secondary markets. The result holds after taking into account the impact on market liquidity or shocks linked to political and economic uncertainty addressing silent issues of social risks. The non-significant empirical results on socialium provide us with a rare opportunity to bridge the reasonings stemming from the financial and sociological approaches. We explain why the issuers and investors still bear an interest for the social bonds through the lens of new institutionalism. Social influences, institutional and mimetic pressures and the acquisition of legitimacy in the eyes of society and stakeholders influence the issuance and the acceptance of social bonds.